Rectovaginal Fistula Due to an Erosive Pessary: A Case Report - Mohamed, Waleed Inayat; Emmanuel, Dorea; Maqbool, Shahzaib; Asad, Ali; Jawad, Asad; Ihtesham, Arham (International Journal of Medical Students, 2022)
Background: Pelvic organ prolapse (POP) occurs when pelvic organs protrude through the vagina due to displacement from their normal anatomic position, as a result of a weakening of the pelvic muscles. Pessaries have long been used to treat POP, but they may result in rectovaginal fistulas as a rare complication. The Case: We report a rare case of a rectovaginal fistula following vaginal ring pessary use in an 82-year-old G7P7 woman. She had a past medical history of bipolar disorder, and initially presented for nursing care and psychiatric support. A trained psychologist evaluated her, and found no psychological morbidity. A two-day history of a fall, diffuse abdominal pain, and chronic urinary incontinence were rather identified. Gynecological pelvic examination revealed a rectovaginal fistula and impacted stools in the vagina. Conclusion: The use of ring pessaries, though a conservative management option for POP, may lead to a rectovaginal fistula, a rare but severe complication.